2019
DOI: 10.1200/jco.2019.37.15_suppl.4079
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab (pembro) for advanced biliary adenocarcinoma: Results from the KEYNOTE-028 (KN028) and KEYNOTE-158 (KN158) basket studies.

Abstract: 4079 Background: Antitumor activity with pembro, an anti–PD-1 antibody, has been observed in patients (pts) with advanced/metastatic biliary tract cancers (BTC), who have limited treatment options. We present follow-up data from pts with advanced BTC treated with pembro in the KN158 (NCT02628067; phase 2) and KN028 (NCT02054806; phase 1) studies. Methods: Eligible pts ≥18 y in the KN158/KN028 BTC cohorts had histologically/cytologically confirmed incurable advanced BTC that progressed after/failed any number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
110
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 0 publications
8
110
0
1
Order By: Relevance
“…In this same study, 34 patients with CPS < 1 received the same treatment, however, tumor control was lower: ORR was only 2.9% and median PFS was 1.9 months [93]. Of note, none of the patients across the two studies were MSI [92]. Interestingly, two cases of complete disease resolution were reported after pembrolizumab alone in second-line treatment [94].…”
Section: Ici Monotherapymentioning
confidence: 87%
See 2 more Smart Citations
“…In this same study, 34 patients with CPS < 1 received the same treatment, however, tumor control was lower: ORR was only 2.9% and median PFS was 1.9 months [93]. Of note, none of the patients across the two studies were MSI [92]. Interestingly, two cases of complete disease resolution were reported after pembrolizumab alone in second-line treatment [94].…”
Section: Ici Monotherapymentioning
confidence: 87%
“…Early studies of ICIs in BTCs, regardless of MSI status, showed the first signal of activity. Pembrolizumab monotherapy has been tested in a phase Ib study in pre-treated patients with PD-L1-positive (>1% positive cells) BTC [92]. Thirty-seven (42%) patients out of 89 screened had PD-L1-positive tumors, and 24 of them received pembrolizumab.…”
Section: Ici Monotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with advanced cholangiocarcinoma or gallbladder adenocarcinoma, results from phase I KEYNOTE-028 and phase II KEYNOTE-158 research indicated that pembrolizumab, a humanized monoclonal antibody against PD-1, constitutes a possible treatment option regardless of PD-L1 expression [14]. The PD-L1 antibody (22C3) and a 1% cutoff level were used in these trials.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research by Neyaz et al [11] and Lin et al [12] has reported inconsistent and contradictory results. Furthermore, although the possibility of immunotherapy has been studied, relevant information in this area is also very limited so far [13,14]. This study aimed to investigate the expression of PD-L1 and determine the potential association with prognostic impact in GBC.…”
mentioning
confidence: 99%